Coagulant and flocculant effect of Opuntia ficus-indica in water treatment (2024)
ABSTRACT: One of the most relevant processes in potable and wastewater treatment plants is coagulation-flocculation,which gives rise to the destabilization of dissolving solids, for the subsequent generation of flocs using a coagulating agent. Aluminum sulfate (Al2(SO4)3) is the most used coagulant internationally, due to its efficiency and low cost. However, its utilization can leave a residue of aluminum in water and bring with it a variety of health problems due to its bioaccumu- lative characteristics, implying both the deterioration of ecosystems and problems for human health. In this regard, it is necessary to establish alternatives that avoid the permanence of this heavy metal in water, so that the mucilage of Opuntia ficus-indica becomes a natural coagulant of great interest. Likewise, it is a sustainable alternative for water treatment, given its characteristics of biodegradability, low toxicity, commercial cost, relative abundance, renewability, and high efficiency, allowing a low generation of sludge, which can be degraded through a fair treatment with a high valuation spectrum.